Is the ex ante risk premium always positive? - Boudoukh, Jacob; Richardson, Matthew; Smith, Tom (Journal of Financial Economics, 1993)
This paper develops tests of inequality restrictions implied by conditional asset pricing models. The methodology is easy to implement, requires little knowledge of the conditional distribution of asset returns, and is valid under fairly weak assumptions. As an application, we test whether the ex ante risk premium is always positive. We report reliable evidence that the ex ante risk premium is negative in some states of the world; these states are related to periods of high expected inflation and especially to downward-sloping term structures.